2017
DOI: 10.1016/j.neo.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

C1QBP Regulates YBX1 to Suppress the Androgen Receptor (AR)-Enhanced RCC Cell Invasion

Abstract: Early studies suggested that the androgen receptor (AR) might play important roles to promote the renal cell carcinoma (RCC) progression; however, the detailed mechanisms remain unclear. Here we demonstrated the higher YBX1 expression with lower C1QBP expression in human RCC clinical tissues, and the intensity of C1QBP was negatively correlated with the YBX1 nuclear expression. Mechanism dissection found C1QBP could interact with YBX1 to suppress the YBX1 activation via altering the YBX1 phosphorylation and nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 45 publications
6
11
0
Order By: Relevance
“…Among the 13 identified survival-associated SFs, HNRNPU, PTBP1, and YBX1 have already been revealed in several RCC-related pathways based on previous studies. [55][56][57] These results suggested that our analyses were partly in accordance with previous research. 53 Besides, in vitro and in vivo studies have revealed that PTBP1 could promote tumor angiogenesis and distal metastasis via activating the hypoxia-inducible factor-1α pathway, indicating its important prognostic role in RCC.…”
Section: Discussionsupporting
confidence: 92%
“…Among the 13 identified survival-associated SFs, HNRNPU, PTBP1, and YBX1 have already been revealed in several RCC-related pathways based on previous studies. [55][56][57] These results suggested that our analyses were partly in accordance with previous research. 53 Besides, in vitro and in vivo studies have revealed that PTBP1 could promote tumor angiogenesis and distal metastasis via activating the hypoxia-inducible factor-1α pathway, indicating its important prognostic role in RCC.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, disease does recur with most patients who unfortunately do succumb to the disease 4. Meanwhile, for patients with renal cell carcinoma (RCC), approximately 30% patients will progress to metastasis after first diagnosed 5. Targeting angiogenetic factors from the VEGF family has become an effective strategy to inhibit tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…They included significant biological pathways, the 10 most significant of which were phosphoprotein, acetylation, protein binding, poly (A) RNA binding, nucleoplasm, isopeptide bond, Ubl conjugation, extracellular exosome, mutagenesis site, and nucleus; the 10 pathways included YBX1 and HNRNPC. YBX1 was once not known to be associated with BRONJ, but then numerous studies reported that it played a role in cancer progression . HNRNPC was also identified as a candidate biomarker for chemoresistance in gastric cancer …”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…YBX1 was once not known to be associated with BRONJ, but then numerous studies reported that it played a role in cancer progression. [39][40][41][42] HNRNPC was also identified as a candidate biomarker for chemoresistance in gastric cancer. 43 There are 2 potential approaches to analyzing gene expression data in microarray studies.…”
Section: Con Clu Sion a N D Discussionmentioning
confidence: 99%